(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current situation and analyze factors affecting the inpatient experience in the General Surgery Department of Le Van Viet Hospital, Ho Chi Minh city, in 2024. Methods: A cross-sectional study with a mixed-methods approach was conducted. Quantitative data were collected from interviews with 172 inpatients using the inpatient experience scale of the Ho Chi Minh city Department of Health. Qualitative data were obtained from 9 in-depth interviews with hospital management and healthcare staff, and 1 focus group discussion with patients. Results: Overall, 83.1% of inpatients reported a positive experience, with the highest scores on healthcare staff’s communication attitude and the lowest on facility conditions. Patients with health insurance had a higher rate of positive experiences (85.3%) compared to those without (62.5%), p < 0.05. Influencing factors included healthcare financing, human resources, information systems, infrastructure, and management. Conclusion: The hospital needs to strengthen security in inpatient areas, review and ensure adequate safety facilities for patients, improve the quality of restrooms, and enhance overall sanitation within the hospital.